Proteomics for Transthyretin (TTR) Related Amyloidosis - Ando, Yukio; Ueda, Mitsuharu (Current Proteomics, 2011)
Of systemic type of amyloidosis, transthyretin (TTR)-related familial amyloidotic polyneuropathy (FAP) is a fatal hereditary amyloidosis with autosomal dominant trait. As of today, reports of 121 different points of mutations or a deletion in the TTR gene have been identified. In addition, senile systemic amyloidosis induced by wild type TTR has been focused in the recent attention. Early diagnosis of FAP is absolutely imperative for the treatments, because duration of the disease is one of the most important prognostic factors for patients' survival after treatments including liver transplantation. To make a diagnosis of FAP sooner, we established a novel rapid diagnostic system. It included histopathological, genetic and proteomic techniques used to detect amyloid deposits in tissues, genetic mutations of the TTR gene, and variant TTR in serum. Mass spectrometric analyses can clearly detect TTR variants in the most of FAP cases and can be used for screening and double checking TTR variants with the genetic testing. In this review, we introduce recent research progress in ATTR amyloidosis and our diagnostic system.
Keywords: genetic testing